2015
DOI: 10.1186/s13068-015-0309-9
|View full text |Cite
|
Sign up to set email alerts
|

Microbial community dynamics in replicate anaerobic digesters exposed sequentially to increasing organic loading rate, acidosis, and process recovery

Abstract: BackgroundVolatile fatty acid intoxication (acidosis), a common process failure recorded in anaerobic reactors, leads to drastic losses in methane production. Unfortunately, little is known about the microbial mechanisms underlining acidosis and the potential to recover the process. In this study, triplicate mesophilic anaerobic reactors of 100 L were exposed to acidosis resulting from an excessive feeding with sugar beet pulp and were compared to a steady-state reactor.ResultsStable operational conditions at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

13
87
2
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 148 publications
(105 citation statements)
references
References 71 publications
13
87
2
3
Order By: Relevance
“…The first three main phyla are reported as part of a core group by numerous authors (Abendroth et al, 2015;Bassani et al, 2015;Duda et al, 2015;Goux et al, 2015). In AD of cattle manure and sludge, some authors (Rivière et al, 2009;St-Pierre and Wright, 2014;Campanaro et al, 2016) reported, as part of the core group, also Cloroflexi, which, on the contrary, we found at 0.03% only.…”
Section: Microbial Community Analysis and Compositioncontrasting
confidence: 52%
“…The first three main phyla are reported as part of a core group by numerous authors (Abendroth et al, 2015;Bassani et al, 2015;Duda et al, 2015;Goux et al, 2015). In AD of cattle manure and sludge, some authors (Rivière et al, 2009;St-Pierre and Wright, 2014;Campanaro et al, 2016) reported, as part of the core group, also Cloroflexi, which, on the contrary, we found at 0.03% only.…”
Section: Microbial Community Analysis and Compositioncontrasting
confidence: 52%
“…During the start-up period, the dominant class was Gammaproteobacteria affiliated with the phylum Proteobacteria, with a relative abundance of 13.67%, followed by Bacteroidia, Clostridia, Anaerolineae and Bacilli, with a relative abundance of 12.87%, 11.88%, 10.96% and 9.89%, respectively. Among these predominant classes, Bacteroidia and Clostridia played significant roles in hydrolysis metabolism [47][48][49]. Gammaproteobacteria was the most representative class during the start-up period, which was also the main contributor to the phylum Proteobacteria.…”
Section: Shifts In Microbial Community Structures With Seasonal Tempementioning
confidence: 99%
“…These results probably indicate that seasonal temperature in summer benefited the growth of Bacilli bacteria. Bacteroidales affiliated with the class Bacteroidia had been identified as hydrolyser and fermenter that participated in the conversation of cellulose and polysaccharide into VFAs [49]. Clostridiales affiliated with the class Clostridia was correlated with methane production, due to their diverse metabolism that utilized polysaccharide fermentation to produce VFAs for methanogenesis [47,48].…”
Section: Shifts In Microbial Community Structures With Seasonal Tempementioning
confidence: 99%
“…The relative abundances of Methanoculleus and Methanosprillum in Lysimeters 1 and 2 were higher than that in Lysimeter 3. Previous studies reported that the predominance of hydrogenotrophic methanogens such as Methanoculleus and Methanosprillum was found under stress conditions, and that it might be related to its tolerance of high ammonia concentrations [38,40,41].…”
Section: Bacteria and Archaea Communities In Lysimetersmentioning
confidence: 96%
“…Clostridia were the most predominant class in Lysimeters 2 and 3 with an abundance of 23.1% and 25.3%, respectively. Bacteroidetes was mainly founded in anaerobic digestion and resistant to adverse environmental conditions such as low pH and temperature [17,38].…”
Section: Bacteria and Archaea Communities In Lysimetersmentioning
confidence: 99%